Impact on service provision for non-invasive cardiac imaging following NICE recommendations: an observational study. Issue 1029 (15th March 2011) - Garg, Pankaj; Ashrafi, Reza; Feeney, Laura; Lagan, Jakub; Wong, Peter; Rodrigues, Erwin; Davis, Gershan
Abstract : Background: Chest pain or discomfort due to angina can have a potentially poor prognosis, emphasising the importance of prompt and accurate diagnosis. The National Institute for Health and Clinical Excellence (NICE) published 'Chest pain of recent onset' guidelines in March 2010. These guidelines appraise the role of newer non-invasive modalities in cardiac imaging in the prompt and cost-effective diagnosis of coronary artery disease. Objective: To study the service requirement for non-invasive cardiac imaging in patients with stable chest pain using current NICE guidance. Design: Single-centre, 6-month (January 2010 to June 2010) observational study. Setting: Rapid access chest pain clinics in a large university teaching hospital providing secondary care cardiology services. Methods: Clinic letters were used to ascertain the type of chest pain and cardiovascular risk factors. The resting 12-lead ECG was examined for any ischaemic changes. Patients were then retrospectively allocated to an assessment pathway based on NICE guidance for the evaluation of stable chest pain. Pretest likelihood of coronary artery disease was calculated using Pryor et al 's table as published by NICE. Depending on the calculated pretest probability, their NICE-suggested investigation was determined. This included no further investigations, cardiac CT, functional imaging or invasive angiography. Results: 500 patients were seen in rapid access chest pain clinics, 65 of which did not meet the referral criteria of having chest pain. On the basis of previous practice, 52% of patients were likely to have an exercise tolerance test. According to current NICE guidance as applied to our cohort of patients, 128 (30%) would have required functional imaging, 119 (27%) no further investigation, 95 (22%) cardiac CT, and 93 (21%) invasive angiography. Conclusion: Functional imaging and then cardiac CT are the main investigations required in the assessment of patients with stable chest pain.